2017
DOI: 10.1111/andr.12348
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acids influence sperm quality and function

Abstract: Recently, obesity has been linked to male infertility. In animal models the administration of a high-fat diet caused a reduction in sperm quality, by impairing gamete energy metabolism. The aim of this study was to investigate a possible effect of dietary fatty acids supplementation in the modulation of sperm energy metabolism and, in turn, in the improvement of sperm quality in rats fed a high-fat diet. Sexually mature male Sprague-Dawley rats were divided into four groups and fed for 4 weeks a standard diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 46 publications
4
48
0
1
Order By: Relevance
“…In conclusion, we show that dietary lipids affect sperm function, especially sperm metabolism, in D. melanogaster, as in vertebrates (Ferramosca, Moscatelli, Giacomo, & Zara, 2017). Future studies will have to genetically target those enzymes in Drosophila that were activated in mice after PUFA supplementation (Ferramosca et al, 2017): sperm enzymes involved in glycolysis, tricarboxylic acid cycle and the respiration chain and that reduce oxidative damage and explore the exciting dynamics of dietary lipid uptake and fertility in the wild.…”
Section: Discussionmentioning
confidence: 83%
“…In conclusion, we show that dietary lipids affect sperm function, especially sperm metabolism, in D. melanogaster, as in vertebrates (Ferramosca, Moscatelli, Giacomo, & Zara, 2017). Future studies will have to genetically target those enzymes in Drosophila that were activated in mice after PUFA supplementation (Ferramosca et al, 2017): sperm enzymes involved in glycolysis, tricarboxylic acid cycle and the respiration chain and that reduce oxidative damage and explore the exciting dynamics of dietary lipid uptake and fertility in the wild.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, KO has the ability to improve lipid and glucose metabolism, exerting possible protective effects against the negative effects caused by a high‐fat diet supplementation . Interestingly, KO administration caused a strong increase in sperm concentration and motility in comparison to high‐fat fed rats . The same study revealed that fatty acid composition of the diet influenced sperm metabolism, by restoring the activity of enzymes involved in sperm bioenergetics pathways.…”
Section: Effects Of Pufa On Sperm Quality and Functionmentioning
confidence: 87%
“…Interestingly, the fat intake increment promotes sperm cell damage, but not the OO intake alone . On the contrary, fat, and OO intake simultaneously recovers normal sperm physiology . In particular, OO supplementation significantly increased sperm motility, without affecting serum glycemic profile and fat distribution observed in high‐fat fed animals.…”
Section: Effects Of Mufa On Sperm Quality and Functionmentioning
confidence: 94%
See 2 more Smart Citations